2-(3-Methyl-2-nitrophenyl)-4,5-dihydro-1,3-oxazole - Lei, Dongwei (International Union of Crystallography, 2008)
In the title compound, C(10)H(10)N(2)O(3), an intermediate in the synthesis of anthranilamide insecticides, all the non-H atoms except the nitro-group O atom lie on a crystallographic mirror plane. The H atoms of the methyl group are disordered over two sets of sites with equal occupancies. In the crystal structure, C—H⋯N links lead to chains of molecules propagating in [100].